A Study on Portfolio Management WRT Textile Industry - et. al., Dr. Seema Nazneena, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Changing global financial environment and emergence of new economic powers in recent decades, diversification of investment portfolios at country and sector levels assumed additional significance. Optimum portfolio selection within a capital market is primarily based on the best risk-return trade-off among the industry sectors. Literature suggests that much of market volatility can be attributed to substantial increase in sector specific and sub-sector specific risks. This research has estimated the dynamics of correlations of stock market returns between Industry sectors in India. Analysis of monthly market data for the period 09-DEC 2020 to 05-FEB 2021 on a sample of 4 industry sectors selected randomly indicates that investors can substantially improve their reward to risk as compared with the market returns.